Transcriptomic Analysis of Resistant and Susceptible Responses in a New Model Root-Knot Nematode Infection System Using Solanum torvum and Meloidogyne arenaria - Sato, Kazuki; Uehara, Taketo; Holbein, Julia; Sasaki-Sekimoto, Yuko; Gan, Pamela; Bino, Takahiro; Yamaguchi, Katsushi; Ichihashi, Yasunori; Maki, Noriko; Shigenobu, Shuji; Ohta, Hiroyuki; Franke, Rochus B.; et al. (Frontiers in Plant Science, 2021)
Root-knot nematodes (RKNs) are among the most devastating pests in agriculture. Solanum torvum Sw. (turkey berry) has been used as a rootstock for eggplant (aubergine) cultivation because of its resistance to RKNs, including Meloidogyne incognita and M. arenaria. We previously found that a pathotype of M. arenaria, A2-J, is able to infect and propagate in S. torvum. In vitro infection assays showed that S. torvum induced the accumulation of brown pigments during avirulent pathotype A2-O infection, but not during virulent A2-J infection. This experimental system is advantageous because resistant and susceptible responses can be distinguished within a few days, and because a single plant genome can yield information about both resistant and susceptible responses. Comparative RNA-sequencing analysis of S. torvum inoculated with A2-J and A2-O at early stages of infection was used to parse the specific resistance and susceptible responses. Infection with A2-J did not induce statistically significant changes in gene expression within one day post-inoculation (DPI), but afterward, A2-J specifically induced the expression of chalcone synthase, spermidine synthase, and genes related to cell wall modification and transmembrane transport. Infection with A2-O rapidly induced the expression of genes encoding class III peroxidases, sesquiterpene synthases, and fatty acid desaturases at 1 DPI, followed by genes involved in defense, hormone signaling, and the biosynthesis of lignin at 3 DPI. Both isolates induced the expression of suberin biosynthetic genes, which may be triggered by wounding during nematode infection. Histochemical analysis revealed that A2-O, but not A2-J, induced lignin accumulation at the root tip, suggesting that physical reinforcement of cell walls with lignin is an important defense response against nematodes. The S. torvum-RKN system can provide a molecular basis for understanding plant-nematode interactions.